The pivotal politics of temporary legislation - Oh, Jason S (Iowa law review, 2015)
Temporary legislation-law that expires on a given date-is an increasingly important part of the policy landscape in areas as diverse as homeland security, gun control, and taxation. Whether temporary legislation is renewed (and just as importantly, whether sophisticated actors expect such legislation to be renewed) is key to understanding its behavioral effects and long-run policy implications. Before we can evaluate the desirability of any piece of temporary legislation, we must first understand the uncertainty surrounding its renewal. This Article fills a gap in the existing literature by providing a theoretical and empirical framework for exploring that uncertainty.